2001
DOI: 10.1037/0022-0663.93.4.758
|View full text |Cite
|
Sign up to set email alerts
|

Turning around reading achievement: Predictors of high school students' academic resilience.

Abstract: In a national, longitudinal database, factors were examined that enabled public school students on a path toward failure to significantly improve reading achievement by high school graduation. Youths who faced the proximal risk of low achievement during the transition to high school were vulnerable to continued low achievement or failure; yet, a small number improved reading proficiency from failing the basic level to passing the intermediate or advanced levels. Being Caucasian, being female, having an interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
2
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 53 publications
(115 reference statements)
3
58
2
5
Order By: Relevance
“…Furthermore, it has been reported that students who are high in internal LoC have better grades and test scores than do students of the same intelligence, who are low in internal LoC (Capell & Weinstein, 2001). Even though Slavin (2006) stated that in reality, students' success could be a product of both external and internal factors (abilities, efforts, task difficulty, teachers' behaviors, etc.…”
Section: Students' Locus Of Control and Its Relationship To Self-esteemmentioning
confidence: 99%
“…Furthermore, it has been reported that students who are high in internal LoC have better grades and test scores than do students of the same intelligence, who are low in internal LoC (Capell & Weinstein, 2001). Even though Slavin (2006) stated that in reality, students' success could be a product of both external and internal factors (abilities, efforts, task difficulty, teachers' behaviors, etc.…”
Section: Students' Locus Of Control and Its Relationship To Self-esteemmentioning
confidence: 99%
“…In many of the studies reviewed, the researchers used total scale scores in a path analysis model when they could have used parcels as indicators in a latent variable model (e.g., Cappella & Weinstein, 2001;Chan, Schmitt, DeShon, Clause, & Delbridge, 1997;Gong, Shenkar, Luo, & Nyaw, 2001;Hill & Fischer, 2001;Kahn, 2001;Lee & Liu, 2001;Lopez, 2001;Macan, 1994;Miller & Byrnes, 2001;Pajares & Miller, 1995;Perrone & Worthington, 2001;Portello & Long, 2001;Rioux & Penner, 2001;Rose & Feldman, 1997;Stice & Barrera, 1995;Weisz, Southam-Gerow, & McCarty, 2001;Whittaker & Robitschek, 2001). In all of these studies, no reason was provided for using a measured variable model rather than a latent variable model.…”
Section: The Use Of Parcels In Applied Researchmentioning
confidence: 99%
“…Resilience has predicted academic attainment in high school students (Capella & Weinsten, 2001;Gonzalez & Padilla, 1997;Martin & Marsh, 2006;Nota, Soresi & Zimmerman, 2004) where the conceptual frameworks of academic resilience and academic buoyancy have been developed to identify factors which may protect against stress (Martin & Marsh, 2008. Personal attributes including relatedness, a sense of mastery and spirituality (Prince-Embury, 2011;Kim & Esquivel, 2011) and support from parents and teachers (Bryan, 2005;Mullis, Rathge & Mullis, 2003;Prince-Embury, 2008) have contributed to resilience being used to underpin mental health services and academic success in school settings (Esquivel, Doll & Oades-Sese, 2011, Doll, Jones, Osborn, Dooley & Turner, 2011.…”
Section: Psychological Resiliencementioning
confidence: 99%